MOF-74 Derived Carbon-Stabilized Pt/Cu-PC-900 Nanoparticles: Ultra-low Pt Content and Improved Electrocatalytic Activity. (1st September 2022) - Parkash, Anand; Islam, Mazharul; Qureshi, Khan Muhammad; Arain, Adeel Mukhtar
Abstract : Fuel cell technology is the best alternative to replace fossil fuels in the modern period. Platinum-based materials may function well as fuel cell electrodes because these can be employed as catalytic materials to carry out the infamous oxygen reduction process. In this respect, a copper-based metal-organic framework (Cu-MOF-74) was first created, to which ultralow content platinum nanoparticles (Pt/Cu-MOF-74) were added, and the structure was then studied using a variety of experimental approaches. After heating the MOF to 900 °C, Pt and Cu nanoparticles are incorporated into it to create a homogenized hybrid functional material, which is then pyrolyzed (Pt-Cu-PC-900). Compared to the 20% Pt/C catalyst available commercially, the Pt/Cu-PC-900 hybrid has shown superior ORR performance in terms of half-wave potential and limiting current density. This study emphasizes the value of nanoparticles with low content of Pt for potential large-scale commercial fuel cell applications.